Primate and Human Evolution - Cachel, Susan (New York : CUP, 2006)
Primate and Human Evolution provides a synthesis of the evolution and adaptive significance of human anatomical, physiological and behavioral traits. Using paleontology and modern human variation and biology, it compares hominid traits to those of other catarrhine primates both living and extinct, presenting a new hominization model that does not depend solely on global climate change, but on predictable trends observed in catarrhines. Dealing with the origins of hominid tool use and tool manufacture, it compares tool behavior in other animals and incorporates information from the earliest archaeological record. Examining the use of non-human primates and other mammals in modeling the origins of early human social behavior, Susan Cachel argues that human intelligence does not arise from complex social interactions, but from attentiveness to the natural world. This book will be a rich source of inspiration for all those interested in the evolution of all primates, including ourselves.
Included References 389-451p.; Index 452-469p.
Keywords: Human evolution; Primates; Anthropology